Kessler, Herbert L. La experiencia del arte medieval. Traducido por Antonia Martínez Ruipérez. Madrid: Akal, 2022 [ISBN: 9788446051435] - Pazos-López, Ángel (Eikón / Imago, 2023)
Reseña de la obra de Kessler, Herbert L. La experiencia del arte medieval. Traducido por Antonia Martínez Ruipérez. Madrid: Akal, 2022 [ISBN: 9788446051435]